Why Not Let Kids Be Kids? An Exploratory Analysis of the Relationship Between Alternative Rationales for Managing Status Offending and Youths’ Self-Concepts - Jennings, Wesley G. (American journal of criminal justice, 2009)
Over the past several decades, the juvenile justice system has struggled with an effective response to status offenders and their unwanted behaviors. Three divergent rationales have emerged for handling these youth: (1) treatment, (2) deterrence, and (3) normalization. Using data from over 300 youth under supervision by agencies in three states, the current study assesses how these differing practices are related to youths’ self-concepts. Results provide support for both deterrence and normalization-based rationales over the historical treatment-based rationale. Viewing status offending as normal adolescent behavior (i.e., normalization) has the most beneficial effect on self-concept. Study limitations and directions for future research are discussed.